Consumers' categorization of eco-friendly consumer goods: an integrative review and research agenda - Larrañaga Muguerza, Arancha; Valor Martínez, Carmen (My University)
Understanding how consumers categorize a consumer good as eco-friendly is key to facilitating consumers' purchasing of products with lower environmental footprints. Scholarship has increasingly addressed this question. However, most research has examined a single cue that prevents the building of a holistic explanation. An integrative review of studies may provide not only a synthesis of the state of the art but also an overarching integrative theoretical framework that explains what cues consumers use to categorize products as green and the mechanisms guiding the interpretation of these cues. This review of 29 studies examining consumers' assessment of eco-friendliness in consumer goods unearths five cues used as surrogate indicators of eco-friendliness. Nevertheless, these cues are not entirely related to the actual environmental footprint of a product based on the life cycle assessment. Drawing from schema categorization theory, an integrative theoretical framework is presented whereby categorization processes are said to be guided by consumers' lay theories. A research agenda is outlined to stimulate new lines of inquiry around lay theories and product attributes.
Artículos en revistas
Keywords: Instituto de Investigación Tecnológica (IIT)